Problems in water The Meaning Of The Ngirim Banyu Tradition As Local Wisdom Of The Community In Claket Village, Mojokerto - Berlian Aprilia; Trio Utami Trio Utami; Elsa Wahyu Nabawi; Sugiantoro Sugiantoro (Program Studi Pendidikan Sejarah - Universitas Samudra, 2026)
This study aims to analyze the meaning of the Ngirim Banyu tradition, which reflects local wisdom in the lives of the Claket Village community. The methodology used in this study is qualitative with a descriptive design. Data were obtained through participatory observation, in-depth interviews with key informants such as the village head, traditional leaders, religious leaders, and community members, as well as documentation studies. Data analysis was conducted using an interactive model that includes data reduction, data presentation, and interpretation, while ensuring data validity through source triangulation. The research findings indicate that the Ngirim Banyu tradition reflects local wisdom values from four perspectives. From a religious perspective, this tradition serves as an expression of gratitude to God for the gift of water. From a social perspective, it strengthens solidarity through collective participation. Culturally, Ngirim Banyu is a time-honored tradition rich in symbols and meaning. Meanwhile, from an ecological perspective, this tradition fosters awareness of the need to preserve water sources. A unique finding of this study lies in the strong integration of spiritual values and ecological awareness within a single traditional practice. Unlike similar traditions, Ngirim Banyu is not merely ritualistic but also serves as a means of fostering concrete behavior in environmental conservation, particularly regarding spring water sources In a cultural context, this tradition serves as a way to transmit values ​​and norms that regulate community behavior from generation to generation. From an ecological perspective, this tradition reflects a shared awareness of preserving water resources based on cultural values. Furthermore, the management of water resources through local institutions demonstrates the interconnectedness between social, cultural, and economic aspects of community life. These findings confirm that the Ngirim Banyu tradition is not only symbolic but also a socio-cultural system that contributes to maintaining a balanced relationship between humans, the environment, and the social structure of society.